A new European record of Diadesmis fukushimae and its transference to Humidophila genus (Bacillariophyta) - Kövér, Csilla; Korponai, János; Harangi, Sándor; Buczkó, Krisztina (Acta Botanica Croatica, 2015)
Diadesmis fukushimae, a rare oligotraphenic diatom, was found in some high mountain lakes of Romania. Its occurrence in the Parâng and Retezat Mountains is the second European record of the species. To date D. fukushimae has been known only from the type locality (Shenandoah National Park, Virginia, USA) and from a spring (Grotta Guernica, Dolomiti Bellunesi National Park (south-eastern Alps, Italy). Investigation by scanning electron microscopy showed that this species should be transferred to the recently established genus Humidophila. A new combination is proposed, Humidophila fukushimae. The morphological details of the European population are also presented.